2020
DOI: 10.1371/journal.pone.0239236
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lower extremity amputation in patients with diabetic foot ulcers: A meta-analysis

Abstract: A considerable number of diabetic foot ulcer (DFU) patients require amputation every year, which worsens their quality of life, aggravates the social burden, and shortens their life expectancy. Considering these negative effects, it is important to explore the relative risk factors affecting amputation in DFU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 48 publications
(31 reference statements)
7
102
4
4
Order By: Relevance
“…In our multivariate analysis, HbA1c was independently associated with amputation. Interestingly, a recent meta-analysis showed that the HbA1c level does not affect the incidence of amputation in patients with diabetic foot ulcers [ 13 ]. Intensive control may decrease the risk of amputation in patients with diabetic foot syndrome [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our multivariate analysis, HbA1c was independently associated with amputation. Interestingly, a recent meta-analysis showed that the HbA1c level does not affect the incidence of amputation in patients with diabetic foot ulcers [ 13 ]. Intensive control may decrease the risk of amputation in patients with diabetic foot syndrome [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age plays an important role in atherosclerosis, resulting in an increased risk of cardiovascular disease. No clear association was observed between age and amputation in patients with diabetic foot ulcers [ 13 ]. We found that age was independently associated with lower limb amputation, which was consistent with a previous study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amputation rate in diabetics is 10–30 times more than that in non-diabetics and account for 69–80% of non-traumatic amputations [ 6 , 7 ]. The risk factors of DFU include age, male, peripheral neuropathy, peripheral vasculopathy, smoking, trauma, history of diabetes for >10 years, and glycated hemoglobin of >7.5%, all of which positively correlate with DFU [ 8 ]. The medical expenditure for DFU is extremely high as it increases the length of hospitalization and the number of emergency and outpatient visits.…”
Section: Introductionmentioning
confidence: 99%